2008
DOI: 10.1097/smj.0b013e31815d28d2
|View full text |Cite
|
Sign up to set email alerts
|

Seeding of the Percutaneous Endoscopic Gastrostomy Tract from Esophageal Squamous Cell Cancer Presenting as an Acutely Bleeding Malignant Gastric Ulcer: A Novel Clinicoendoscopic Presentation

Abstract: The current novel report of significant upper gastrointestinal bleeding from a malignant gastric ulcer at the PEG insertion site, that required blood transfusions, extends the clinicoendoscopic spectrum of peristomal metastases after PEG. Peristomal ulcers occurring in this circumstance should be biopsied at an initial or follow-up EGD, despite the recent gastrointestinal bleeding, to exclude malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Endoscopic appearances of gastric stomal metastases include a homogeneous small mass, "well-healed" stomal scar, large exophytic mass, ulcerated mass, or excavated ulcer (17). Mean survival after diagnosis was 4.3 ± 3.8 months (range 1-16 months, N = 28 patients).…”
Section: Clinical Presentationmentioning
confidence: 96%
See 2 more Smart Citations
“…Endoscopic appearances of gastric stomal metastases include a homogeneous small mass, "well-healed" stomal scar, large exophytic mass, ulcerated mass, or excavated ulcer (17). Mean survival after diagnosis was 4.3 ± 3.8 months (range 1-16 months, N = 28 patients).…”
Section: Clinical Presentationmentioning
confidence: 96%
“…This time lag presumably reflects the time required for exfoliated and implanted cancerous cell(s) to multiply to become grossly evident. In five (11%) cases, stomal metastases were diagnosed after PEG removal (mean 5.8 ± 4.0 months thereafter, range 2-10 months (7,14,17,26,32)). The clinical presentation of stomal metastases on the abdominal wall or the gastric wall is described in Table 1A and B, respectively.…”
Section: Clinical Presentationmentioning
confidence: 98%
See 1 more Smart Citation
“…Like most surgical procedures, PEG placement has associated morbidity; however, most complications are minor . Interestingly, a complication unique to PEG placement in HNC is metastases at the gastrostomy site, occurring in only 0.5%‐3.0% of patients with HNC . First to reported in 1989, the metastasis of squamous cell carcinoma of the head and neck to the PEG site occurred after using the Gauderer‐Ponsky “pull” method; however, Alagaratnam had previously reported the metastasis of HNC to the gastrostomy site in 1977, following an open approach .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Interestingly, a complication unique to PEG placement in HNC is metastases at the gastrostomy site, occurring in only 0.5%-3.0% of patients with HNC. 3,[9][10][11] First to reported in 1989, the metastasis of squamous cell carcinoma of the head and neck to the PEG site occurred after using the Gauderer-Ponsky "pull" method; however, Alagaratnam had previously reported the metastasis of HNC to the gastrostomy site in 1977, following an open approach. 5,12 A review of the literature concerning this rare complication revealed that only 62 cases of metastases of head and neck squamous cell carcinoma to the PEG site have been previously described, including Preyer's initial report.…”
Section: Introductionmentioning
confidence: 99%